Prostate volume and prostate-specific antigen in men with Parkinson's disease are not different compared to age-matched control group: A prospective, case-controlled multicenter study - Yu Seob Shin; Hwang Choi; Min Woo Cheon; Seung Chol Park; Jong Kwan Park; Hyung Jin Kim; Young Beom Jeong (Prostate International, 2015)
Purpose: Patients with Parkinson's disease (PD) suffer from gait disturbance as well as lower urinary tract symptoms (LUTS). There have been no reports that evaluated the prostate volume (PV) and prostate-specific antigen (PSA) of patients with PD. In this study, we prospectively evaluated PV and PSA in men with PD. Methods: From May 2009 to January 2012, 60 PD patients and 60 age-matched non-PD patients with LUTS enrolled at three centers in Korea. All participants (PD as well as non-PD patients) had LUTS at presentation. We measured the PV using a transrectal ultrasonography and checked the serum PSA level in patients with PD and their non-PD counterparts, who served as the age-matched control group, and then compared the data of both groups. Patients with abnormal digital rectal examination results and/or serum PSA levels >4.0 ng/mL underwent prostate biopsy. Results: The mean patient age was 71.37 ± 7.36 years and 70.85 ± 6.31 years for PD and non-PD patients (P = 0.651), respectively. There were no significant statistical differences between the two groups in terms of total PV (28.56 ± 14.59 in PD vs. 29.21 ± 10.41 in non-PD, P = 0.727), transition zone PV (12.72 ± 8.76 vs. 12.73 ± 6.68, P = 0.993), and total serum PSA (1.88 ± 2.80 vs. 2.01 ± 2.02, P = 0.759). In the PD group, seven patients had PSA levels >4.0 ng/mL (range, 4.12–11.18 ng/mL). Among these patients, prostate cancer (PC) was detected in two patients. In the non-PD group, PSA levels >4.0 ng/mL were detected in nine patients (range, 4.16–8.28 ng/mL). Among these patients, PC was detected in three patients. The PC occurrence rate was similar in both groups. Conclusions: Our data show that a neurologic lesion causing PD does not affect PV and PSA. As both groups have a similar PC occurrence rate, it is clear that prostate evaluation is necessary for PD as well as non-PD patients.